Family-specific degenerate primer design: a tool to design consensus degenerated oligonucleotides - Iserte, Javier Alonso (2013)
Designing degenerate PCR primers for templates of unknown nucleotide sequence may be a very difficult task. In this paper, we present a new method to design degenerate primers, implemented in family-specific degenerate primer design (FAS-DPD) computer software, for which the starting point is a multiple alignment of related amino acids or nucleotide sequences. To assess their efficiency, four different genome collections were used, covering a wide range of genomic lengths: Arenavirus ( nucleotides), Baculovirus ( to  bp), Lactobacillus sp. ( to  bp), and Pseudomonas sp. ( to  bp). In each case, FAS-DPD designed primers were tested computationally to measure specificity. Designed primers for Arenavirus and Baculovirus were tested experimentally. The method presented here is useful for designing degenerate primers on collections of related protein sequences, allowing detection of new family members.